Stategi Manajemen Sumber Daya Manusia Dalam Meningkatkan Keunggulan Bersaing Perusahaan (CV. Wibisono Kreatif Media) - Nila Mashluha Sukma Nahdliyana; Zsa Zsa Izazi (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
By coordinating with the overarching business plan, human resource management assists companies in accomplishing both short- and long-term objectives. Because of this, the purpose of this paper is to explain how Human Resource Management (HRM) and business strategy relate to one another and to give a summary of effective staff development and training programs that boost workplace efficiency. Using methods for gathering data from library studies, the research approach is qualitative. According to the study, contingency theory underpins the notion that business strategy and HRM practices are closely related. This theory emphasizes how the business's competitive strategy influences the methods of human resource management that are selected. A carefully thought-out business plan functions in accordance with the primary goal and vision.